Peran Bank Indonesia Terhadap Binaan Usaha Mikro Kecil dan Menengah di Kota Kupang - Laurensia Murin Boro; Pius Bumi Kellen; Fransina W.Ballo (Universitas Veteran Bangun Nusantara, 2024)
Bank Indonesia is a Central Bank that stabilizes the value of the rupiah against an asset and has an important role in supporting Micro, Small and Medium Enterprises (MSMEs). Some of the coaching activities carried out by Bank Indonesia are: providing training to MSMEs, increasing access to financing, increasing competitiveness, and partnerships with financial institutions. The purpose of this study is to find out the role of Bank Indonesia in the development of MSMEs, and to identify and further analyze the role of BI for the development of MSMEs around the city of Kupang. This research is a qualitative descriptive research, data collected through interviews, and documentation. This study focuses on the role of Bank Indonesia in fostering MSMEs in Kupang City by looking at how the implementation of working capital product financing based on performance and increasing turnover and profits and how it affects MSME actors and the impact on MSMEs themselves. The results of the study show that with the guidance from Bank Indonesia for MSMEs in Kupang City has a positive impact both in terms of increasing turnover and the facilities provided by Bank Indonesia to MSME actors where before getting the Foster, MSME actors have difficulty in arranging routine transactions and developing their various products, besides that MSME actors also have difficulties in keeping up with market developments, especially for business actors who are just starting their business. However, after getting Coaching and Financing, business actors began to be able to compete and follow market developments.